Contributions of prof. dr Petar Kostic for the Development and Improvement of Psychological Measuring Instruments in the Republic of Serbia - Ranželović, Dušan; Kostić, Senka (Collection of Papers of the Faculty of Philosophy in Priština, 2020)
Professor dr Petar Kostic was concerned with constructing, auditing and adapting instruments from various aspects of complete human psychology: from personality, through general cognitive abilities, but also specific abilities, to instruments whic record a some version of soc The aim of the paper was to present the contributions that made Professor Peter Kostic as a someone who is a important for psychometrics as a scientific branch in the field of psychological sciences. Some of the measuring instruments Professor Kosticworked on – whether as an author, auditor or predictor - have been described, analyzed and critically reviewed. We presented three instruments that relate to the three dominant domains of examining an individual's psychological traits: personality traits (Basic Personality Support - BOL), occupational determinations (Test of professional commitment - TPO), and cognitive abilities (Universal Aptitude Test - UTS). In addition to presenting and analyzing the aforementioned instruments, the paper also providesexamples of published empirical research in which the researcher was used these instruments and thus confirmed their scientific contribution. Apart from the indisputable professional contribution reflected in the widespread use of the aforementioned instruments in psychological practice in the military, clinic, centers for social work, schools, etc., as well as the individual use of the instruments by practicing psychologists, we also consider no less important a use value of these instruments in scientific research. Finally, we gave a critical review of Professor Kostic's overall contribution to the development of psychometrics in Serbia. Particularly emphasized is the motive of Professor Kostic, who guided the construction of the instruments described and analyzed here, as well as all others on which he worked directly or indirectly, which was of a purely professional, professional and scientific char acter. As the best proof that Professor Kostic had no  financial motive when he was constructing these instruments is the fact that in the last years of his life he made available the complete instruments as well as manuals for their use to the psychological, and above allscientificty community, leaving them open for use on his site: www.psihometric.com.
Keywords: prof. dr Petar Kostic; psychometry; BOL; TPO; UTS